2014
DOI: 10.1002/ieam.1575
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metals, metalloids, and ash mixture toxicity using sediment toxicity testing

Abstract: In December 2008, a release of 4.1 million m3 of coal ash from the Tennessee Valley Authority Kingston Fossil Plant occurred. Ash washed into the Emory River and migrated downstream into the Clinch and Tennessee Rivers. A Baseline Ecological Risk Assessment evaluated risks to ecological receptors from ash in the river system post‐dredging. This article describes the approach used and results from sediment toxicity tests, discussing any causal relationships between ash, metals, and toxicity. Literature is limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The 17 receptor groups evaluated included fish, benthic invertebrates, aquatic plants (periphyton and macrophytes), and wildlife that feed in and around the river system (see conceptual site model in Figure 2 in Walls, Jones et al 2015, this issue). BERA details are available in the project report (ARCADIS ), and details for several receptors are presented in 5 other articles in this series (Buys et al , Meyer et al , Rigg et al , Stojak et al , Walls, Meyer et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The 17 receptor groups evaluated included fish, benthic invertebrates, aquatic plants (periphyton and macrophytes), and wildlife that feed in and around the river system (see conceptual site model in Figure 2 in Walls, Jones et al 2015, this issue). BERA details are available in the project report (ARCADIS ), and details for several receptors are presented in 5 other articles in this series (Buys et al , Meyer et al , Rigg et al , Stojak et al , Walls, Meyer et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The colocated sediment data collected in 2011 found that while benthic community composition was mostly correlated with substrate types and water depth, 3 individual samples in the immediate area of the release appeared to have associated adverse benthic community effects potentially related to fly ash. Metals in sediment ash is of concern in other studies, as mentioned throughout this series (Stojak et al , this issue) especially when ash is present at greater than 40%. These 3 samples demonstrate the heterogeneous nature of these areas still containing pockets of ash.…”
Section: Discussionmentioning
confidence: 76%
“…Based on the colocated sediment samples collected with the benthic invertebrate community samples, approximately 5.5% of the samples had ash content exceeding 40%. The 40% threshold was derived from sediment toxicity tests (Stojak et al , this issue). The only samples which had a community response slightly correlated to ash and metals content ranged from 62‐65% ash, much greater than the 40% laboratory threshold.…”
Section: Discussionmentioning
confidence: 99%
“…These various types of samples were used to estimate bioavailability and bioaccumulation of COPECs from diet and other exposure pathways, as well as to model bioavailability to the respective predators. Subsequent articles focus on the evaluations for fish (Rigg et al , this issue), benthic invertebrates (Buys et al , this issue, and Stojak et al , this issue), aquatic‐ and riparian‐feeding wildlife (Meyer et al , this issue), and aerial‐feeding insectivores (i.e., tree swallows; Walls et al , this issue).…”
Section: Study Approachmentioning
confidence: 99%